TRAPPED XE AND I-XE AGES IN AQUEOUSLY ALTERED CV3 METEORITES - Hohenberg C.M.; Pravdivtseva O.V.; Meshik A.P. (My University, 2004)
Twenty-two dark inclusions (DIs) from Allende (18), Leoville (2), Vigarano (1) and Efremovka (1) were studied by the I-Xe method. All except two of these DIs (Vigarano 2226 and Leoville LV2) produce well-defined isochrons, and precise I-Xe ages. The Allende DIs formed a tight group about 1.6 Ma older than Shallowater (4.566 ± 0.002 Ga), about 5 Ma older than four previously studied Allende CAIs. Most of the dark inclusions require trapped Xe with less 129Xe (or more 128Xe) than conventional planetary Xe (well restricted in composition by Q-Xe or OC-Xe). Studies of an irradiated/unirradiated DI pair from Allende demonstrate that the 128Xe/132Xe ratio in trapped is normal planetary, so that a 129Xe/132Xe ratio below planetary seems to be required. Yet, this is not possible given constraints on 129Xe evolution in the early solar system. Trends among all of the Allende DIs suggest that an intimate mixture of partially decayed iodine and Xe formed a pseudo trapped Xe component enriched in both 129Xe and 127I, and subsequently in 128Xe after n-capture during reactor irradiation. Enrichment in radiogenic 129Xe, but with a 129Xe/127I ratio less than that observed in the iodine host phase, places closure of this trapped mixture ≥13 Ma after precipitation of the major iodine-bearing phase. Because the I-Xe isochron is a mixing line between iodine-derived and trapped Xe (pseudo or not), I-Xe ages, given by the slope of this mixing line, are not compromised by the presence of pseudo trapped Xe, and the precision of the I-Xe ages is given by the statistics of the line fit.